Note—Finding Certain Weakly-Efficient Vertices in Multiple Objective Linear Fractional Programming - Benson, Harold P. (Management Science, 1985)
Recently Kornbluth and Steuer have developed a simplex-based algorithm for finding all weakly-efficient vertices of an augmented feasible region of a multiple objective linear fractional programming problem. As part of this algorithm, they presented a method for detecting certain weakly-efficient vertices called break points. In this note we show that the procedure used by Kornbluth and Steuer in this method for computing the numbers needed to find these break points may sometimes fail. We also propose a fail-safe method for computing these numbers and give some computational results with this method.